0795 The Relationship Between Restless Legs Syndrome and Hypothyroidism. (27th May 2020) - Ahmed, N; Kandil, M; Elfil, M; Jamal, A; Koo, B
Abstract: Introduction: The diurnal nature of RLS and its response to dopamine hint that hormones may be central in RLS pathophysiology. Hypothyroidism has been linked to RLS, but studies are few and limited in scope. We sought to determine whether restless legs syndrome (RLS) is more prevalent in persons with hypothyroidism and whether hypothyroidism is more prevalent in persons with RLS. Methods: Persons with hypothyroidism and controls without hypothyroidism were recruited through Research Match, an on-line registry of potential clinical research participants, and assessed for RLS using the Cambridge Hopkins questionnaire. Persons with RLS and controls without RLS were recruited through the RLS Foundation and Research Match and assessed for hypothyroidism by self-report of physician diagnosis. RLS severity was assessed using the International RLS Study Group Severity Scale and cause of hypothyroidism was assessed by self-report. Results: 266 hypothyroid subjects and 321 controls were comparable in age (52.3±13.4 vs. 53.9±11.7; p=0.14) and gender (91.7% vs. 91.3% women; p=0.85). 354 RLS and 313 control subjects were comparable in age (59.1±13.2 vs. 58.2±13.6; p=0.41) and gender (80.8% vs. 78.3%; p=0.42). Hypothyroid participants compared to controls had significantly higher RLS prevalence (14.3% vs. 8.1%; p=0.02). RLS participants compared to non-RLS controls had significantly higher hypothyroidism prevalence (22.3% vs. 13.8%; p=0.005). RLS severity was similar in persons with and those without hypothyroidism. Among 73 persons with RLS and comorbid hypothyroidism, 14 previously were hyperthyroid compared to 0 out of 37 persons with hypothyroidism without RLS (p=0.004). Conclusion: RLS prevalence is increased in individuals with hypothyroidism and hypothyroidism prevalence is increased in individuals with RLS. Persons with comorbid hypothyroidism and RLS are significantly more likely than those with hypothyroidism alone to have had hyperthyroidism prior to hypothyroidism. The association between RLS and thyroid disease is likely to shed light on the complex biological mechanisms underlying RLS pathophysiology. Support: None